Contact Allergy in Canada Versus United States: Analysis of the North American Contact Dermatitis Group Data 2005–2016. Issue 6 (November 2021) - Atwater, Amber Reck; Ward, Jordan Maxwell; Liu, Beiyu; Warshaw, Erin M.; DeKoven, Joel G.; Silverberg, Jonathan I.; Taylor, James S.; Belsito, Donald V.; Fowler, Joseph F.; Maibach, Howard I.; Reeder, Margo J.; Pratt, Melanie D.; et al.
Abstract : Background: Differences in consumer product availability, distribution, and use may lead to national differences in contact sensitization frequencies. Objective: The aim of the study was to describe the differences in contact allergy between the United States (US) and Canada. Methods: This is a retrospective cross-sectional analysis of the North American Contact Dermatitis Group data from 2005 to 2016. Frequencies of demographics, clinical characteristics, positive reactions, trends, and occupations were calculated. Results: A total of 28, 640 patients underwent patch testing. At least 1 positive patch test was observed in 18, 599 patients (US, 11, 641 [66.5%]; Canada, 6958 [62.5%]). When comparing the 2 groups, US positive reactions were more likely to occur in male patients (odds ratio [OR] = 1.40, 95% confidence interval [CI] = 1.31–1.49), older than 40 years (OR = 1.30, 95% CI = 1.22–1.38), Black (OR = 2.67, 95% CI = 2.24–3.19) or Hispanic race (OR = 3.53, 95% CI = 2.61–4.78), and/or patients with scattered generalized dermatitis (OR = 1.96, 95% CI = 1.80–2.13). They were less likely to occur in patients with eczema (OR = 0.61, 95% CI = 0.57–0.65) and Asian race (OR = 0.50, 95% CI = 0.44–0.56). Nickel (US, 16.0%; Canada, 22.4%) and methylisothiazolinone (US, 13.4%; Canada, 11.0%) were the top allergens. The third most frequent was neomycin (US, 11.7%) and fragrance mix I (Canada, 10.2%). Conclusions: National differences in allergen prevalence and trends exist in North America.